Islamic interbank money market: contracts, instruments and their pricing - Saiti, Buerhan; Hasan, Aznan; Engku Ali, Engku Rabiah Adawiah (Palgrave Macmillan, 2016)
This chapter discusses the Islamic interbank money market, its instruments and operations. The discussion demonstrates that the existence of a viable Islamic interbank money market is crucial for the successful implementation of an Islamic financial system. The chapter examines the various interbank money market instruments, their underlying Islamic contracts and their pricing mechanisms, with appropriate examples. The availability of various Islamic interbank money market instruments allows Islamic banks to cover their exposure (in case of deficit) and make placement on shortterm basis (in case of surplus). Moving forward, a greater variety of instruments with fixed return mechanisms and tradability features, which at the same time invite fewer Shariah issues, must be offered in the market to ensure a more vibrant Islamic interbank money market.